2023
DOI: 10.21873/invivo.13066
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarker Establishment for Evaluation of Excessive Fructose Consumption Using a Rat Model

Abstract: Background/Aim: The habitual consumption of excessive fructose is associated with the onset and progression of lifestyle-related diseases, such as nonalcoholic fatty liver disease (NAFLD). In this study, we investigated the physiological changes observed when consuming a diet containing excessive fructose on the viewpoints of hepatotoxicity biological markers using a rat model and explored the biomarker candidates that could detect the effects of excessive fructose intake at an early stage. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Given that NAFLD is asymptomatic (24), we must take appropriate action to ensure that individuals avoid daily excessive fructose intake, and develop effective tools to diagnose daily excessive fructose intake. Our previous study demonstrated that four weeks of HFrD consumption in rats caused hepatic hypertrophy with lipid accumulation, as well as a significant increase in L-ALP activity and a significant decrease in I-ALP in the blood (11). I-ALP activity decreased from the first week of HFrD in vivo 37: 1967-1974 (2023) 1970…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Given that NAFLD is asymptomatic (24), we must take appropriate action to ensure that individuals avoid daily excessive fructose intake, and develop effective tools to diagnose daily excessive fructose intake. Our previous study demonstrated that four weeks of HFrD consumption in rats caused hepatic hypertrophy with lipid accumulation, as well as a significant increase in L-ALP activity and a significant decrease in I-ALP in the blood (11). I-ALP activity decreased from the first week of HFrD in vivo 37: 1967-1974 (2023) 1970…”
Section: Discussionmentioning
confidence: 98%
“…Animals and housing environments. In our previous study in sixweek-old rats, we measured the activity of ALP isozymes in blood collected during the light period (sleep phase) after four weeks of HFrD feeding (11). The purpose of this study was to evaluate whether variations in ALP isozyme activity occurred between the light (sleep) and dark (active) periods after 1 week of consuming a HFrD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations